Tourism and protected areas from the perspective of the international environmental - Kosieradzka-Federczyk, Agata (Studia Ecologiae et Bioethicae, 2018)
The article presents selected issues concerning tourist activity in protected areas because of natural values. The issues were presented in light of selected documents of international environmental law, which show great interest on the part of international law in the preparation of guidelines and best practices in order to raise awareness of the importance of tourist management for the proper protection of such areas. Sustainable tourism is argued to be the answer to the identified problems.